(untitled) (Western European Journal of Linguistics and Education, 2024)
The widespread use of computer technologies in automated systems of information processing and management has intensified the problem of protecting information circulating in computer systems from unauthorized access. Information protection in computer systems has a number of specific features related to the fact that information is not strictly connected to mass media, it can be easily and quickly copied and transmitted through communication channels. A large number of threats to information are known, which can be carried out by both external attackers and internal attackers.